Transformasi Pendidikan Literasi dan Kebahasaan dengan Teknologi: Meningkatkan Kualitas Pembelajaran Generasi Z - Lestari, Suci Ayu (Universitas Tanjungpura, 2024)
This study examines the application of technology in literacy and language education to enhance the learning quality of the technology-savvy Generation Z. The method employed is a literature review, analyzing journal articles and related research. The results indicate that interactive learning applications, e-learning platforms, and social media increase students' interest and engagement. Technology also creates an interactive and collaborative learning environment, aligning with the active learning styles of Generation Z. Additionally, technology contributes to improved academic achievement and creativity among students. This research recommends that educators and educational institutions integrate innovative technology into their teaching practices. Training for teachers is also deemed essential to maximize the use of technology. The findings suggest that the implementation of technology in literacy and language education can help address the challenges of learning in the digital age